Analysis and Modeling of Queuing System Simulation in Payment Process at Minimarket (Case Study of Minimarket X Yogyakarta) - Trinopi Melani; Yani Iriani (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this study is to analyze the queuing system at Minimarket X so as to minimize the number of queues. The method in this writing uses a discrete event simulation method with the help of Anylogic software. Simulation is used as a method to analyze problems that exist in the payment system at the Minimarket, while Anylogic software as an illustration that can facilitate the queuing system so that it is clearer and easier to understand. Observations conducted for 20 days show that the queuing system applied by Minimarket X is Multi Channel – Single Phase and First Come First Served (FCFS) or First In First Out (FIFO) with 4 cashier officers (M/M/4). Each cashier is tasked with serving customers and processing the products purchased by scanning them and packing each grocery. The average number of Minimarket visitors every day is 22 customers per hour with a queue length of 10 to 11 customers per hour, and the average waiting time for customers to be served is around 27 to 30 minutes. The simulation used through anylogic software obtained error results within 67 minutes 43 seconds.